What's your favorite animal? - Carle, Eric (New York, New York : Henry Holt and Company, 2014)
" Eric Carle Nick Bruel Lucy Cousins Susan Jeffers Steven Kellogg Jon Klassen Tom Lichtenheld Peter McCarty Chris Raschka Peter Si;s Lane Smith Erin Stead Rosemary Wells Mo Willems Everybody has a favorite animal. Some like little white dogs or big black cats or hoppy brown bunnies best. Others prefer squishy snails or tall giraffes or sleek black panthers. With beautiful illustrations and charming personal stories, 14 children's book artists share their favorite animals and why they love them"--
Keywords: Animals in art -- Juvenile literature; JUVENILE NONFICTION / Animals / General; JUVENILE NONFICTION / Art / General